2022
DOI: 10.3390/bs12060197
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Voice Outcomes: The Configurational Analysis of the Effects of LMX and Peer Relationships

Abstract: From the perspective of social relationships, this study extends the understanding of employee voice by examining voice outcomes, especially a voicer’s influence in their work team. In particular, we explore how two different social relationships, LMX and peer relationship, separately and jointly affect the ‘voice-influence’ relationship. Drawing on social network theory, we propose that higher LMX and central positions in peer networks (i.e., centrality in the friendship network) strengthen the positive impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…We conducted logistic regression using the kim package in R (Kim, 2022) to model attendance from users’ online polarization scores for Brexit-relevant and general tweets, respectively, social validation (likes) on Brexit-relevant and general tweets during each time period, and their social connectedness online (number of accounts they followed). By including a polarization score for general tweets as well as Brexit-relevant tweets, we thus controlled for polarization in general tweets, accounting for the extent to which a user might display, for example, changes in “mobilizing content in general” versus “mobilizing content about Brexit” relative to other users in the sample.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted logistic regression using the kim package in R (Kim, 2022) to model attendance from users’ online polarization scores for Brexit-relevant and general tweets, respectively, social validation (likes) on Brexit-relevant and general tweets during each time period, and their social connectedness online (number of accounts they followed). By including a polarization score for general tweets as well as Brexit-relevant tweets, we thus controlled for polarization in general tweets, accounting for the extent to which a user might display, for example, changes in “mobilizing content in general” versus “mobilizing content about Brexit” relative to other users in the sample.…”
Section: Methodsmentioning
confidence: 99%
“…However, past studies have demonstrated that close peers and acquaintances can help each other achieve their social and emotional goals (Tse and Dasborough, 2008). Employees who speak up may have trouble getting along with their coworkers (Kim et al, 2022a), because doing so sometimes requires calling attention to the shortcomings of other team members. As a result, coworkers who are close to one another may not voice up in an effort to protect their peers and avoid conflicts.…”
Section: Source(s): Created By Authorsmentioning
confidence: 99%
“…Hence, those on the fence may manage the inherent risks of upward voice with peer support (Jing et al, 2023). However, speaking out to proximal peers may result in leaders being excluded from the decision-making process, which can lower LMX (Kim et al, 2022a). As a result, it is imperative for management to carefully design equitable LMX linkages to ensure bottom-up communication.…”
Section: Practical Implicationsmentioning
confidence: 99%